Decolonizing Method of Hadith Matn Criticism on the Case of Aisha’s Age at Marriage in Western Scholarship - Prayogi, Ananda; Fahmi, Wildan Ulumul (Proceedings of International Conference on Muslim Society and Thought, 2024)
This paper critically engages with the methodological frameworks utilized in Western scholarship concerning the age of Aisha at the time of her marriage to Prophet Muhammad. Within the context of contemporary Western modernism, which has introduced new ethical standards and norms previously absent but now regarded as authoritative, this study aims to scrutinize the impact of such norms on interpretations within Hadith scholarship. Through a decolonial lens applied to the criticism of Hadith matn, it seeks to unravel and challenge colonial biases and Eurocentric perspectives that have historically shaped scholarly discourse on this issue. Furthermore, this research highlights the contributions and perspectives of prominent figures in Western Hadith scholarship, including Jonathan AC Brown, to enrich the dialogue on the subject. By advocating for a decolonized approach to Hadith criticism, this study underscores the necessity of contextual understanding, cultural sensitivity, and epistemic inclusivity in the examination of Islamic history and tradition.